Feasibility and acceptability of a multi-domain intervention to increase Mediterranean diet adherence and physical activity in older UK adults at risk of dementia: protocol for the MedEx-UK randomised controlled trial. Issue 2 (5th February 2021) - Shannon, Oliver M; Lee, Vivian; Bundy, Rafe; Gillings, Rachel; Jennings, Amy; Stephan, Blossom; Hornberger, Michael; Balanos, George; Paddick, Stella Maria; Hanson, Sarah; Hardeman, Wendy; Holmes, Rebecca; et al.
Abstract : Introduction: Dementia prevalence continues to increase, and effective interventions are needed to prevent, delay or slow its progression. Higher adherence to the Mediterranean diet (MedDiet) and increased physical activity (PA) have been proposed as strategies to facilitate healthy brain ageing and reduce dementia risk. However, to date, there have been no dementia prevention trials in the UK focussed on combined dietary and PA interventions. This study aims to: (1) assess feasibility and acceptability of a theory-underpinned digital and group-based intervention for dementia risk reduction in an 'at risk' UK cohort; (2) evaluate behaviour change responses to the intervention; and, (3) provide information on cognitive, neurological, vascular and physiological outcomes to inform the design of a follow-on, full-scale efficacy trial. Methods: One hundred and eight participants aged 55 to 74 years with a QRISK2 score of ≥10% will be recruited to take part in this 24-week multi-site study. Participants will be randomised into three parallel arms: (1) Control; (2) MedDiet; and, (3) MedDiet+PA. The study will evaluate a personalised website, group session and food delivery intervention to increase MedDiet adherence and PA in older adults at risk of dementia. Diet and PA will be monitored prior to, during and following the intervention. Feasibility, acceptability and hypothesised mediators will be assessed in addition to measures of cognitive function, brain structure/perfusion (MRI), vascular function and metabolic markers (blood, urine and faecal) prior to, and following, the intervention. Discussion: This trial will provide insights into the feasibility, acceptability and mechanism of effect of a multi-domain intervention focussed on the MedDiet alone and PA for dementia risk reduction in an 'at risk' UK cohort. Ethics and dissemination: The study has received NHS REC and HRA approval (18/NI/0191). Findings will be disseminated via conference presentations, public lectures, and peer-reviewed publications. Trial registration details: ClinicalTrials.gov NCT03673722 .